Patient influencers' promotion of prescription drugs on Instagram: Effects of illness disclosure on persuasion knowledge through narrative transportation. Issue 8 (17th November 2022) - Kim, Hyosun
Abstract: Via two experiments, the present study examined how patient influencers' illness disclosure in their sponsored posts of prescription drug ads predicts individuals' persuasion knowledge and behavioral intentions. Study 1 (N = 206) revealed that influencers' illness disclosure predicted attitudinal persuasion knowledge through transportation and parasocial interaction, further suggesting that illness disclosure reduces persuasion knowledge, causing people to perceive prescription drug ads on Instagram as less promotional. Study 2 (N = 181) replicated the mediating roles of transportation and parasocial interaction, demonstrating that first-person voice (vs. third-person) illness narrative in a patient influencer's medical device promotion on Instagram significantly predicted transportation, which then enhanced parasocial interaction with the influencer to influence eWOM intention as well as help-seeking intention. The two experiments demonstrate how influencers' illness disclosure narratives affect persuasion knowledge and online behavioral intention as well as real-life behavioral intention. Supplemental data for this article is available online at https://doi.org/10.1080/02650487.2022.2054614 .